Toward a postcolonial reading of the Epistle of James James 2:1-13 in its Roman imperial context - Mongstad-Kvammen, Ingeborg 1972- (Boston Brill, 2013)
Preliminary Material -- Introduction -- 1. The Epistle of James—Preliminary Considerations -- 2. Situating the Present Investigation within Recent Jamesian Research -- 3. Social and Cultural Texture: A Short Overview of Roman Political History and Markers of Social Affiliation -- 4. Exegesis of James 2:1–13 -- 5. Ideological Texture: Toward a Postcolonial Reading on James 2:1–13 -- 6. Conclusions -- Bibliography -- Index of Modern Authors -- Index of Subjects and Names -- Index of Ancient Sources.
Toward a Postcolonial Reading of the Epistle of James offers an interpretation of Jas 2:1-13 putting the text in the midst of the Roman imperial system of rank. This study shows that the conflict of the text has more to do with differences of rank than poverty and wealth. The main problem is that the Christian assemblies are acting according to Roman cultural etiquette instead of their Jewish-Christian heritage when a Roman equestrian and a beggar visit the assembly. The members of the assemblies are accused of having become too Roman. From a postcolonial perspective, this is a typical case of hybrid identities. Additional key concepts from postcolonialism, such as diaspora, ‘othering’, naming of oppressors, and binarisms such as coloniser/colonised, centre/margin, honour/shame and power/powerless, are highlighted throughout the study
Includes bibliographical references and index. - Description based on print version record
Keywords: Bible -- Postcolonial criticism; Bible -- Postcolonial criticism; RELIGION / Biblical Studies / New Testament; RELIGION / Biblical Studies / Paul's Letters